Assessing Indonesian students’ competence in translating French texts of different types - Setiadi, Riswanda (Universitas Pendidikan Indonesia, 2018)
This research is based on the fact that while learning a foreign language, translation ability is important for various purposes, yet not easy for the learners to acquire. This study was therefore aimed to: (1) identify the difficulties facing the students in translating different types of texts, especially descriptive, narrative and argumentative; (2) measure the student's ability to translate the text of three different types; and (4) provide feedback to the faculty about the students’ ability to translate descriptive text, narrative and argumentative texts in particular. For the purpose of this study, only non-fiction texts were provided for the students. And it is assumed that different text types require them to take different ways of translating. The subjects were 30 students of the Department of French Language Education, at a state education university in Bandung, who attended a French-Indonesian Translation class. Data collecting instrument used was a translation test consisting descriptive, narrative and argumentative texts to be translated from French into Indonesian. The findings showed that half of the students had difficulty translating the three types of text, particularly in paragraph cohesion and fairness criteria. But they were more able to translate narrative and argumentative texts than descriptive text due to text structure and characteristics as well as students’ lack of vocabulary acquisition. However, in general the students had a slightly sufficient ability to translate those three text types from French into Indonesian. Errors in translation were also identified in relation to their knowledge of both source and target languages.